2007
DOI: 10.1002/ajmg.b.30437
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the brain‐derived neurotropic factor (BDNF) gene in attention deficit hyperactivity disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is a prevalent neurodevelopmental childhood psychiatric disorder. Brain-derived neurotropic factor (BDNF) has been suggested to play a role in the pathogenesis of ADHD and two family-based association studies demonstrated an association of BDNF polymorphisms with ADHD. The aim of the current study was to investigate the BDNF gene for association with ADHD in a large sample of families from Toronto. The transmission of three polymorphisms of the BDNF gene (rs6265,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
5
23
0
Order By: Relevance
“…While Lanktree et al (2008) found evidence for a contribution of the Val allele, Conner et al (2008) showed no association between this polymorphism and adult ADHD scores. Similarly no association between the Val 66 Met SNP and ADHD was detected by Schimmelmann et al (2007) who studied 468 children from 294 families (comprising one or more affected siblings) or by Lee et al (2007) who examined 315 ADHD children from 266 nuclear families. Three genome-wide association studies (GWAS) have been reported for ADHD so far, one used a DNA pooling approach with 343 adult ADHD patients and 304 controls (Lesch et al 2008), another used 958 affected family trios with child ADHD siblings ) and the other, 896 cases with DSM-IV ADHD and 2455 controls (Neale et al 2010a).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While Lanktree et al (2008) found evidence for a contribution of the Val allele, Conner et al (2008) showed no association between this polymorphism and adult ADHD scores. Similarly no association between the Val 66 Met SNP and ADHD was detected by Schimmelmann et al (2007) who studied 468 children from 294 families (comprising one or more affected siblings) or by Lee et al (2007) who examined 315 ADHD children from 266 nuclear families. Three genome-wide association studies (GWAS) have been reported for ADHD so far, one used a DNA pooling approach with 343 adult ADHD patients and 304 controls (Lesch et al 2008), another used 958 affected family trios with child ADHD siblings ) and the other, 896 cases with DSM-IV ADHD and 2455 controls (Neale et al 2010a).…”
Section: Discussionmentioning
confidence: 98%
“…Yet, one German study and two meta-analyses using diverse populations with ADHD failed to replicate preferential transmission of specific BDNF alleles (Forero et al 2009 ;Sanchez-Mora et al 2010 ;Schimmelmann et al 2007). Further, several other association studies have tested the possible involvement of other BDNF polymorphisms in ADHD with conflicting results (Conner et al 2008 ;Kim et al 2007 ;Lanktree et al 2008 ;LaskySu et al 2007 ;Lee et al 2007 ;Ribases et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…37 Moreover, the present BDNF SNP (rs2049046) has also been used to investigate whether its allelic variants were associated with several mental health outcomes, such as attention deficit hyperactivity disorder, autism, obsessivecompulsive disorder and migraine. [40][41][42] PON1 codes for an enzyme that inhibits oxidation of lipoproteins through hydrolysis of lipid peroxides. Such oxidative damage can be induced by methylmercury.…”
Section: Discussionmentioning
confidence: 99%
“…Four TDT (Brookes et al 2006a;Kent et al 2005;Lee et al 2007;Schimmelmann et al 2007) and four Case-Control/HHRR Guan et al 2008;Xu et al 2007b) studies were identiWed for meta-analysis that tested for association between this Val66Met polymorphism and ADHD. Based on previous research (Egan et al 2003;Kent et al 2005), the 'G' or Valine allele was designated as the 'risk' allele.…”
Section: Brain Derived Neurotrophic Factor Gene (Bdnf)mentioning
confidence: 99%